2003
DOI: 10.1090/s0002-9939-03-07002-3
|View full text |Cite
|
Sign up to set email alerts
|

A proof of Nogura’s conjecture

Abstract: Abstract. Answering a question of T. Nogura (1985), we show using the Open Coloring Axiom that the weak diagonal sequence property is preserved by taking products whenever the products themselves are Fréchet. As an application we show, using the same assumption, that the product of two Fréchet groups is Fréchet provided it is sequential. Recall that the product of two Fréchet groups may not be sequential.Recall that a given topological space X (implicitly assumed to be at least Hausdorff) is sequential if ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…There is one case, namely implication 8 in the chart for n ≥ 2, where we know it is both consistent with and independent of ZFC that the implication reverses. The consistent reversal follows from the following result of Todorcevic [19], which answered a question of Nogura [10].…”
Section: Selection Principle Versionsmentioning
confidence: 67%
“…There is one case, namely implication 8 in the chart for n ≥ 2, where we know it is both consistent with and independent of ZFC that the implication reverses. The consistent reversal follows from the following result of Todorcevic [19], which answered a question of Nogura [10].…”
Section: Selection Principle Versionsmentioning
confidence: 67%
“…First, [75] he showed that assuming CH such spaces can be constructed, and later in joint work with Tironi, [81], gave partial results in the opposite direction. The final solution to the problem was given by Stevo Todorčević in [120] extending the approach of Simon and Tironi: the Open Colouring Axiom implies a positive answer.…”
Section: Convergence Propertiesmentioning
confidence: 99%
“…While Malykhin's problem can only have a consistent positive solution and Theorem 2.1 is a ZFC theorem, the analysis of the combinatorial difficulties seems likely to be similar. The reader is referred to [12] and [16] for applications of OCA which are closely related to the subject matter.…”
Section: The Role Of Gapsmentioning
confidence: 99%